2014
DOI: 10.1088/0004-637x/797/2/119
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Exozodiacal Luminosity Function of Main-Sequence Stars: Complete Results From the Keck Nuller Mid-Infrared Surveys

Abstract: Forty-seven nearby main-sequence stars were surveyed with the Keck Interferometer mid-infrared Nulling instrument (KIN) between 2008 and 2011, searching for faint resolved emission from exozodiacal dust. Observations of a subset of the sample have already been reported, focusing essentially on stars with no previously known dust.Here we extend this previous analysis to the whole KIN sample, including 22 more stars with known near-and/or far-infrared excesses. In addition to an analysis similar to that of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 84 publications
8
124
0
Order By: Relevance
“…This favours PR-drag as a good explanation as it is relatively insensitive to the properties of the parent belt. In addition, Mennesson et al [76] show that the observed mid-IR excesses are compatible with PR-drag levels expected from Wyatt [121]. Figure 12 shows the vertical optical depth as a function of the radial distance to the star that is expected from the interplay between PR-drag and collisions from an outer belt located at different initial positions (different colours) and for two different stellar masses (dashed and solid lines).…”
Section: Pr-dragsupporting
confidence: 66%
See 1 more Smart Citation
“…This favours PR-drag as a good explanation as it is relatively insensitive to the properties of the parent belt. In addition, Mennesson et al [76] show that the observed mid-IR excesses are compatible with PR-drag levels expected from Wyatt [121]. Figure 12 shows the vertical optical depth as a function of the radial distance to the star that is expected from the interplay between PR-drag and collisions from an outer belt located at different initial positions (different colours) and for two different stellar masses (dashed and solid lines).…”
Section: Pr-dragsupporting
confidence: 66%
“…Regarding the occurrence of warm exozodis around stars with no previously detected far infrared excess (i.e. no outer dust reservoir), Mennesson et al [76] derived that the median dust level has to be below 60 times the solar value with high confidence (95%, assuming a log-normal luminosity distribution). To go beyond this state-of-the-art exozodi sensitivity, Downloaded by [University of Liege] at 05: 23 25 October 2017 NASA has funded the Large Binocular Telescope Interferometer (LBTI) to carry out a survey in the N' band (9.81-12.41 µm) on 40-50 carefully chosen nearby main-sequence stars [96].…”
Section: Resolved Observations In the Mid-infraredmentioning
confidence: 99%
“…Mid-infrared (mid-IR) nulling observations reveal no correlation between near-IR and mid-IR excesses (Mennesson et al 2014) and follow-up observations of the near-IR excess stars, A&A 595, A44 (2016) attempting to detect polarized scattered light emission from the circumstellar dust, did not result in significant detections (Marshall et al 2016). When combined with the near-IR detections, these data provide strong and valuable constraints -even in the case of upper limits -on the emission at different wavelengths and on different spatial scales, and thus on the origin of the excesses (Lebreton et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming for instance that 36 stars are observed by LBTI with an individual measurement uncertainty of 12 zodis, the final uncertainty on the sample median would be of the order of that 2 zodis limit. In comparison, the current best estimate for the median exozodi level of solar-type stars is 12 +/-24 zodis, as derived from the Keck Interferometer observations of 20 solar-type stars between 2008 and 2011, at a typical accuracy level of 100 to 150 zodis per star 7 . This shows that a tenfold improvement over the state of the art is required of LBTI measurements to properly assess the risk of confusing exo-Earths in the habitable zone with bright exozodi clumps.…”
Section: Introductionmentioning
confidence: 89%